Optimization study of thermal-storage PV-CSP integrated system based on GA-PSO algorithm - Liu, Hongtao; Zhai, Rongrong; Fu, Jiaxin; Wang, Yulong; Yang, Yongping (Solar energy, 2019)
•PV nominal power, power output point and TES capacity are optimized by GA-PSO.•Operating performances are more superior and steadier for CON strategy than IND.•A large-scale PV subsystem is needed for IND strategy in most conditions.•Dispatch strategy should be selected before optimization procedure. In thermal-storage photovoltaic-concentrated solar power (PV-CSP) systems, the fluctuant part electricity is stored in thermal energy storage (TES) system instead of high-cost batteries. In this research, PV nominal power, system power output point and TES capacity in different dispatch strategies are optimized by GA-PSO to achieve a minimized levelized cost of electricity. Then, more power output points are set in each strategy, operating performance and optimal configuration in these complex strategies are studied. After that, optimal configurations and operating characteristics in different heliostats and PV panels cost are explored, and the battery bank is considered. Results show that for the selected CSP subsystem in constant-output strategy, in which CSP power responds to PV power output to provide a constant system power curve, the optimal PV nominal power is 35.23 MW, system power output point is at the CSP-rated power and LCOE is 16.93 ¢/kWh. For independent-output strategy, in which CSP and PV provide power independently, optimal PV nominal power is 213.91 MW, PV power output point is 76.10 MW and LCOE is 16.33 ¢/kWh. For constant-output strategy with one (50% load) or three (75%, 50%, 25% load) middle power output points settled, the optimal systems based on these complex strategies can reach a lower LCOE of 15.32 ¢/kWh and 15.15 ¢/kWh, respectively. In independent-output strategy, LCOE of optimal systems based on complex strategies is 14.33 ¢/kWh and 12.80 ¢/kWh, respectively. In general, the operating performance are more superior and steadier for CON strategy and a large-scale PV subsystem is needed for IND strategy in most conditions.